Analisis Tingkat Suku Bunga Bi Terhadap Jumlah Simpanan Yang Dapat Dihimpun Studi Kasus Terhadap Deposito Berjangka Rupiah (Pada Bank Umum di Indonesia) - Gedriana, Rianika; Arifin, Moch (Jurnal Ilmiah Manajemen Kesatuan, 2016)
Indonesian Banking is currently experiencing significant growth, when seen from fund collections, fund management and credit allocations. A bank’s main function has the obligation to collect funds, one of which is through current accounts. This is a relatively easy method in collecting third party’s funds. The research is aimed to uncover the link of BI rate with the rupiah allocation of fund in Indonesian banks, and how far it is affecting the decision of savings and current accounts. This study is conducted using descriptive and quantitative analysis of the data obtained from Bank of Indonesia statistics. The results show. The results using the correlation method for one-month rupiah deposits, r = -0.2384, 3-month rupiah deposits, r = -0.6108, 6-month rupiah deposits, r = -0.1615, and for rupiah deposits 12 months, r = 0,9775 this show that r = -0, the relationship x and y is negative and very strong (the opposite relationship x and y). However, when looking for savings by the method of research the results of correlation r = -0.795, indicating that the relationship x and y is also negative and very strong. From the analysis of hypothesis testing (Test T) obtained T calculated for each deposit period is 0.8852 (one month), - 0.0069 (3 months), -0.0102 (6 months), -0.0259 ( > = 12 months), whereas for savings products -4, 7319, assuming a 95% confidence value, then count assessed T is smaller than the T table by 2.16. Where it is indicated that H0 accepted, Ha rejected the hypothesis stated interest rate does not affect the amount of deposit and savings.